Social Relations and Relational Incentives - Robert Dur; Jan Tichem (Tinbergen Institute, 2012)
This paper studies how social relationships between managers and employees affect relational incentive contracts. To this end we develop a simple dynamic principal-agent model where both players may have feelings of altruism or spite toward each other. The contract may contain two types of incentives for the agent to work hard: a bonus and a threat of dismissal. We find that good social relationships undermine the credibility of a threat of dismissal but strengthen the credibility of a bonus. Among others, these two mechanisms imply that better social relationships sometimes lead to higher bonuses, while worse social relationships may increase productivity and players' utility in equilibrium.
urn:NBN:nl:ui:15-1765/32667
Keywords: D23; J33; M52; M55; 330; Altruism; spite; social relations; incentives; relational contracts; efficiency wages; subjective performance evaluation; Nash bargaining; Arbeitsbeziehungen; Soziale Beziehungen; Leistungsanreiz; Unvollständiger Vertrag; Prinzipal-Agent-Theorie; Dynamisches Spiel; Verhandlungstheorie; Theorie